Operation petticoat [videorecording (DVD)] - Edwards, Blake, 1922-2010; Grant, Cary, 1904-1986; Curtis, Tony, 1925-2010; O'Brien, Joan, 1936- (Cary Grant collection., 2001)
World War 2 comedy about a submarine commander who finds himself stuck with a decrepit (and pink) sub, a con-man executive officer and a group of Army nurses.